2015
DOI: 10.15376/biores.10.4.7970-7984
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturability of Wood Plastic Composite Sheets on the Basis of the Post-Processing Cooling Curve

Abstract: Extruded wood-plastic composites (WPCs) are increasingly regarded as promising materials for future manufacturing industries. It is necessary to select and tune the post-processing methods to be able to utilize these materials fully. In this development, temperature-related material properties and the cooling rate are important indicators. This paper presents the results of natural cooling in a factory environment fit into a cooling curve function with temperature zones for forming, cutting, and packaging over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Manufacturers often anneal the WPC profiles to reduce the final shrinkage of products (Klyosov 2007). On the basis of the present study, annealing the composite material before the reheating cycles could be suggested to minimize the residual shrinking effect.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Manufacturers often anneal the WPC profiles to reduce the final shrinkage of products (Klyosov 2007). On the basis of the present study, annealing the composite material before the reheating cycles could be suggested to minimize the residual shrinking effect.…”
Section: Discussionmentioning
confidence: 89%
“…The material recipe, density, extrusion speed, and downstream pooling have a direct effect on the shrinkage rate of a WPC (Klyosov 2007). However, the used measurement method and logic control can be utilized with other thermoplastic fiber composite materials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations